Penyaluran Zakat Pendidikan dan Kesesuaiannya dengan Fatwa MUI No. 120/MU/II/1996 tentang Pemberian Dana Zakat untuk Beasiswa Pendidikan dan Undang-undang No. 23 tahun 2011 tentang Pengelolaan Zakat di Baznas Pusat - Firda Hasanatul Auza (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The distribution of zakat funds in 2020 has increased and decreased, then, we can see that in May and December there has been a drastic increase compared to other months. Thus, the distribution of education zakat funds from month to month and even year to year has increased, although the monthly sometimes increases and decreases from the distribution. Meanwhile, the distribution of education zakat funds in 2021 at BAZNAS every month has increased and decreased, which we know that in February the distribution of zakat funds increased from the previous month, followed by the following month in March-May experienced an increase, then the following month in June-December experienced an increase and decrease. The purpose of this study is to find out the Distribution of Education Zakat and its Conformity with MUI Fatwa No. Kep. 120/MUI/II/1996 concerning the Provision of Zakat Funds for Education Scholarships and Law No. 23 of 2011 concerning the Management of Zakat in the Central BAZNAS